Assessment of Sediment Distribution Patterns and Management Strategies in the Porong River Estuary, Sidoarjo - Tania C. M. Lake; Sumiadi; Dian Sisinggih (Postgraduate, University of Mataram, 2026)
This study aims to identify the water surface profile of the Kali Porong River, analyze changes in riverbed contours at the Kali Porong estuary, and propose appropriate mitigation measures for sediment deposition in the estuarine area. The research methodology involves hydraulic and sediment transport modeling using one-dimensional (1D) and two-dimensional (2D) HEC-RAS, supported by Google Earth image interpretation, cross-section analysis, and riverbed elevation data evaluation. The results indicate significant morphological changes in the Kali Porong River during the period 2013–2023. The upstream and middle reaches tend to experience riverbed degradation due to increased flow energy, while the downstream and estuary segments undergo intensive aggradation, characterized by channel shallowing and delta expansion toward the sea. These riverbed changes directly affect the water surface profile and flow velocity, with the 2023 condition showing relatively higher flow velocities compared to those in 2013. Two-dimensional modeling results suggest that the river system has shifted from a dynamic equilibrium condition toward a morphological imbalance. Based on these findings, mitigation measures are recommended in the form of targeted dredging and the construction of sediment control structures at the estuary to maintain channel stability and reduce long-term sedimentation risks.